(untitled) (Latakia University Journal -Medical Sciences Series, 2022)
Aim of the study: The aim of this study is to study the effect of administration of finasteride in benign prostatic hyperplasia patients on bleeding during and after transurethral resection of prostate. Introduction: Transurethral resection of the prostate is considered the standard technique for patients with moderate or severe lower urinary tract symptoms related to benign prostatic hyperplasia (BPH). Pathologically BPH is characterized by increased proliferation of stromal and acinar cells, sustained by increased vascularization (neoangiogenesis). Recent studies have also shown that finasteride reduces angiogenesis and prostatic bleeding associated with BPH. Reducing the volume as a final step in reducing neoangiogenesis could thus represent a fundamental advance in limiting intra- and postoperative bleeding in patients undergoing transurethral resection of the prostate (TURP). Materials and Methods: Our study included 84 patients undergoing TURP between June 2021 and June 2022. Of the patients, 35 received pretreatment with finasteride while 49 did not undergo any pretreatment (control group). In all the patients we evaluated the degree of peri-surgical bleeding, intended as a reduction in hemoglobin values in the 24 h following surgery. Results and Conclusions: In the group of patients pretreated with finasteride(average age 66.3 years), blood loss, evaluated as a reduction in hemoglobin values, was minimal, and only one of the patients(2.8) required blood transfusion. Hemoglobin loss in the 24 h following surgery was 1.1% .In the control group (average age 65.8 years), 5 patients (10.2%) required blood transfusion. The loss of hemoglobin was 2.1%. Finasteride, therefore, seems to play fundamental role in the pretreatment of TURP patients, since by educing dihydrotestosterone synthesis, it interacts with endothelial growth factors, thus reducing angiogenesis and preventing bleeding.